Effect of Different Levels of Nitrogen, Phosphorus and Potash on Growth and Yield of Anjan Grass (Cenchrus ciliaris) - Faroda, A S (Annals of Arid Zone, 2016)
( i ) Significantly more plant height, green and dry matter production were obtained with increasing levels of nitrogen. However, there was no significant difference in tillering due to nitrogen application. (ii ) Phosphorus and potash application did not give significant response to anjan grass. (ili) Application of 20 kg N/ha was economical for anjan grass under semi-arid condition.